Penerapan Pemberian Posisi dan Nesting terhadap Perubahan Suhu Tubuh, Saturasi Oksigenasi dan Frekuensi Nadi pada Bayi dengan Berat Badan Lahir Rendah di Ruang Perinatologi RSUD Batang - Sri Rahayu; Rahayu Winarti (Journal of Health, Medical, and Psychological Studies, 2026)
Low birth weight (LBW) infants are at risk of physiological disorders such as hypothermia, unstable oxygen saturation, and hemodynamic disorders due to limited adaptation to the environment outside the womb. This study aims to determine the effect of positioning and nesting on changes in body temperature, oxygen saturation, and heart rate in LBW infants. The method used was a descriptive case study with a one-group pretest–posttest approach on five LBW infants treated in the Perinatology Unit of Batang Regional General Hospital. The nesting and positioning interventions were administered for three consecutive days, with each session lasting 30 minutes. Physiological parameters were measured before and after the intervention using a digital thermometer, neonatal pulse oximeter, and stethoscope. The results showed an increase in average body temperature from 35.8°C to 36.6°C, oxygen saturation from 94.8% to 98.2%, and heart rate from 130.8 to 136.8 beats per minute within normal limits. It was concluded that positioning and nesting are effective as non-pharmacological therapies to support the physiological stability of LBW infants.